Development of a Student Worksheet Based on Project-Based Learning to Improve Learning Outcomes of Junior High School Students - Rahmah, Yuniarti Khairini; Hafizah, Ellyna; Annur, Syubhan (Jurnal Pijar Mipa, 2025)
This research involves the development of a Student Worksheet based on project-based learning for the solar system sub-material, focusing on improving the learning outcomes of junior high school students. The purpose of this study is to identify the level of validity, practicality, and effectiveness of the project-based learning Student Worksheet. The method employed in this research is Research and Development (R&D), utilising the ADDIE approach as the development model. This study demonstrates that project-based learning, specifically the Student Worksheet on solar system sub-materials, is deemed highly valid, with a validity value of 0.88, aimed at enhancing student learning outcomes. The practicality of the results from a student response questionnaire, with 82.24% of students agreeing, indicates that the Student Worksheet is highly practical. Effectiveness based on knowledge learning outcomes, with the calculation of n-gain from pretest and posttest, obtained an average n-gain of 0.71 with high criteria, attitude learning outcomes obtained an average of 90.67% which is categorised as very good, and learning outcomes skills obtained an average of 91% which is categorized as very good. The results of the study demonstrate that the Student Worksheet project-based learning on the solar system sub-material is feasible for use, as it meets the criteria of validity, practicality, and effectiveness in improving student learning outcomes. The implications of this research suggest that project-based learning Student worksheets can serve as an alternative, innovative teaching material that encourages active student involvement, improves critical thinking skills, and provides educators with a reference for developing learning tools that align with the demands of the Independent Curriculum and 21st-century learning.